Presenting research reflexivity in your PhD thesis - Davis, Dilla (Nurse researcher, 2020)
Background It is important for researchers to be open and transparent about the relationship between themselves and the subjects of their enquiry. Reflexivity enables them to do this, but although there is much guidance in the literature about reflexivity in general, there is little guidance for PhD candidates on including it in their theses.Aim To provide a practical illustration of how researchers can evidence reflexivity in their theses.Discussion The author presents the reflexive stance and journey she made when completing a PhD study that used constructivist grounded theory. It predominantly depicts the influences on the choices and decisions she made, so the reader can make sense of the journey she undertook. The author depicts how she began her journey as a novice nurse researcher and concluded it as a fully fledged researcher.Conclusion There has been much debate about how to integrate reflexivity in the context of a particular study. This article highlights the importance of reflexivity in research and uses excerpts from the author’s thesis to illustrate how it can be presented in a thesis.Implications for practice The article provides a guide and questions for PhD candidates to consider so they can present and think more deeply about reflexivity in their theses.